Concept of Siravedha and its Clinical Application in Different Surgical Diseases (AYUSHDHARA, 2024)
Two fundamental tenets of Ayurvedic medicine are Sodhan and Saman Chikitsa. The root (originating factor) of the body is Rakta and body is sustained verily by blood and as such it should be protected carefully; in fact blood is life. Pitta Dosha and Rakta Dhatu have Ashraya Ashrayi relation with each other, hence increase and decrease of Rakta Dhatu depends on increase and decrease of Pitta Dosha. Rakta Pardoshaj Vikar is primarily caused by vitiation of Pitta Dosha. Among different types of Shodhan therapies, Rakthamokshana is considered as best for Pitta and Rakta Pradoshaj Vyadhi. In Ayurveda, Siravedhana used in the Sarvadehika dushthi of Dosha that means vitiation of Dosha all over the body. In the Shalyatantra Siravedhana has played very important role in the management of various Shakhagata Roga. But Siravedhana has plays main role in the management of disease caused by vitiation of Pitta and Rakta Dushti Vikara. Therefore in Ayurveda especially in the Shalyatantra called the Ardhachikitsa. Since Acharya Sushruta provided a thorough explanation of Pracchan and Siravedhan as well as their significance in Raktagata Vikar, all of the requirements for Siravedhan as stated by Acharyas are included in this topic.